The Impact of Caffeic Acid Phenethyl Ester on Spinal Cord Inflammation in Mice Model of Multiple Sclerosis: Impact of Caffeic Acid Phenethyl Ester in Multiple Sclerosis - Alnawajha , Amin; Endharti , Agustina; Santoso , Sanarto; Santosaningsih , Dewi (Journal of Tropical Life Science, 2024)
Since the majority of the current therapies lack effectiveness and efficiency in treating Multiple Sclerosis, in addition to their high cost, monitoring during usage, and the serious side effects associated with using this therapy, which in some cases may be fatal, for these reasons, there is a necessary need for effective therapy in the clinical setting and searching for an alternative therapy that is effective and safe. For this purpose, this study evaluated the impact and efficiency of Caffeic acid phenethyl ester(CAPE) in the amelioration of inflammation and demyelination in the spinal cord of experimental autoimmune encephalomyelitis(EAE) mouse model multiple sclerosis, which could be a candidate therapy for MS. Multiple sclerosis is an autoimmune T-cell mediated disease, that T- cells become active, and differentiate into Th subset.α4β1integrin increased on the surface of T- cell during inflammation, which regulates immune cell cross through the blood-brain barrier into the central nervous system, and causes inflammation in the brain and spinal cord, myelin sheath damage and neuron demyelination. The in-vivo experiment used mice. The twenty-five mice were divided into control negative, control positive, and three treatment groups. After this, EAE was induced in mice by injecting myelin oligodendrocyte glycoprotein peptide. The mice were monitored and scored daily for clinical signs. CAPE was orally administered to mice at 5 mg/kg for T1, 10 mg/kg for T2, and 20 mg/kg for T3 for 14 days. Immunofluorescence was used to assess α4integrin, Immunohistochemistry (IHC) was used to evaluate infiltration of CD3-T cell marker, and Luxol Fast Blue stain was used to evaluate demyelination. We found that CAPE treated mice model had a reduced infiltration of immune cells, demyelination in the spinal cord mice model, and decreasing α4integrin expression. These findings strongly demonstrated that CAPE could be a potential therapy for Multiple sclerosis, as it ameliorated the inflammation and demyelination in mice models.